Larval parasitism in outbreaking and non-outbreaking populations of Epirrita autumnata (Lepidoptera, Geometridae) - Ruohomäki, Kai (Entomologica Fennica, 1994)
Larval parasitism of Epirrita autumnata (Borkhausen) was monitored during six years in field samples from within the outbreak range of E. autumnata in northern Fennoscandia, and outside it in southern Finland. All parasitoids found were hymenopterans. Six phenologically early species of parasitoids were found in populations within the outbreak range and three species outside the outbreak range. Two late larval parasitoid species were found within the outbreak range, but none outside the outbreak range. In half of the populations within the outbreak range, early larval parasitoids seemed to increase with a time lag. This is consistent with the cyclic population fluctuations of E. autumnata there. On a small spatial scale (among trees), however, parasitoids acted without a time lag. Parasitism rates by the early larval parasitoids are probably too low (mean 11%) for early parasitoids alone to keep densities of E. autumnata continuously at low levels outside the outbreak range in southern Finland.